Visual Inspection of Welding Joints: Analysis of the Causes of Welding Defects and Solutions for Repair. - Firmansyah Sulistiyono; Susilawati; Muhamad Kamaludin; Fauzaan Dwi Nugroho Raharjo (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2025)
The development of technology in the increasingly advanced construction sector cannot be separated from welding, because it has an important role in metal engineering and repair.. There are several factors that affect the quality of welding results, including welding procedures, materials, electrodes, and types of welds used. Inspection of welding results can be done in several ways, one of which is by visual inspection. The TWI Acceptance Criteria standard is used as a reference in determining the quality of welding results in this study. The results of the study showed that four out of five welding defects did not pass the test. This indicates the importance of mastering welding techniques and quality control in the production process. A welder must have competencies that are in accordance with the specifications of his work. Routine inspections and the use of reference standards such as the TWI Acceptance Criteria should be applied to ensure the quality of welding results, both on an educational, training, and industrial scale.